Water‐Resistant Conformal Hybrid Electrodes for Aquatic Endurable Electrocardiographic Monitoring - Ji, Shaobo; Wan, Changjin; Wang, Ting; Li, Qingsong; Chen, Geng; Wang, Jianwu; Liu, Zhiyuan; Yang, Hui; Liu, Xijian; Chen, Xiaodong (Advanced materials (Weinheim), 2020)
Underwater vital signs monitoring of respiratory rate, blood pressure, and the heart's status is essential for healthcare and sports management. Real‐time electrocardiography (ECG) monitoring underwater can be one solution for this. However, the current electrodes used for ECGs are not suitable for aquatic applications since they may lose their adhesiveness to skin, stable conductivity, or/and structural stability when immersed into water. Here, the design and fabrication of water‐resistant electrodes to repurpose stretchable electrodes for applications in an aquatic environment are reported. The electrodes are composed of stretchable metal–polymer composite film as the substrate and dopamine‐containing polymer as a coating. The polymer is designed to possess underwater adhesiveness from the dopamine motif, water stability from the main scaffold, and ionic conductivity from the carboxyl groups for signal transmission. Stable underwater conductivity and firm adhesion to skin allow the electrodes to collect reliable ECG signals under various conditions in water. It is shown that wearable devices incorporated with the water‐resistant electrodes can acquire real‐time ECG signals during swimming, which can be used for revealing the heart condition. These water‐resistant electrodes realize underwater detection of ECG signals and can be used for health monitoring and sports management during aquatic activities. Water‐resistant stretchable electrodes are fabricated with a specially designed polymer. The polymer is adhesive underwater to bridge the electrode and skin, and ionic‐conductive to transmit electrophysiological signals. The conformal electrodes realize reliable electrocardiography (ECG) detection when moving the body or being impacted with water flow, which enables stable wireless real‐time ECG collection during swimming with a wearable device.